Seni Pegelaran Wayang dalam Perspektif Fikih dan Spiritualitas Seni Islam Seyyed Hossein Nasr - Muhammad Riduwan Masykur; Achmad Khudori Soleh (Muslim Heritage, 2023)
AbstractThe function of wayang in the context of ancient times was a means of worship and an intermediary in worshiping God. Whereas in Islam, it is not permissible to worship God by means of means or media, so this becomes a shirk to Allah, over time wayang changes its function, which is contrary to the past, and becomes more adaptive to the times. The purpose of writing this article is to discuss the art of wayang from the perspective of Islamic law or fiqh and in the study of the spirituality of Islamic art Seyyed Hossein Nasr. The writing of this article uses the library research method and literature sources that are in line with the discussion. This research resulted in findings that 1) wayang is an indigenous culture of the archipelago, which at first glance contradicts the views of Islamic jurisprudence and art by Seyyed Hossein Nasr 2) Wayang is an archipelago culture that has a great influence, in the perspective of fiqh, wayang performances are a form of Islamic art based on culture because of their use value today as art without associating partners with Allah., 3) From the perspective of Islamic art Seyyed Hossein Nasr Wayang is classified as a traditional Islamic art as its function is used in educational media through stories that are interesting and seem unique, the existence of wayang that can bring people to their goals Islamic art makes wayang used by walisongo as an effective preaching medium.Â AbstrakFungsi wayang dalam konteks zaman dahulu menjadi sarana ibadah dan perantara dalam menyembah Tuhan. Sedangkan dalam islam tidak diperkenankan menyembah Tuhan dengan menggunakan sarana atau media, sehingga hal tersebut menjadi syirik kepada Allah, seiring berjalannya waktu Wayang beralih fungsi yang bertolak belakang dengan zaman dahulu, dan menjadi lebih adaptif dengan perkembangan zaman. Tujuan penulisan artikel ini adalah untuk membahas seni rupa wayang dalam kacamata hukum islam atau fiqih dan dalam kajian spiritualitas seni islam Seyyed Hossein Nasr. Penulisan artikel ini menggunakan metode library research dan sumber literatur yang selaras dengan pembahasan. Penelitian ini menghasilkan temuan bahwa 1) wayang merupakan budaya asli Nusantara yang sekilas bertentengan dengan pandangan fiqih dan seni islam Seyyed Hossein Nasr 2) Wayang merupakan budaya Nusantara yang memiliki pengaruh yang besar, dalam perspektif fiqih, pagelaran Wayang merupakan salah satu bentuk seni islam berlandaskan budaya karena nilai kegunaannya pada zaman sekarang sebagai seni tanpa unsur menyekutukan Allah, 3) Dari perspektif seni islam Seyyed Hossein Nasr Wayang diklasifikasikan sebagai seni tradisional islam sebagaimana fungsinya yang digunakan dalam media pendidikan melalui cerita yang menarik dan terkesan unik, eksistensi wayang yang dapat membawa manusia kepada tujuan seni islam menjadikan wayang digunakan walisongo sebagai media berdakwah yang efektif.